Household incomes and redistribution in the European Union: quantifying the equalising properties of taxes and benefits - Herwig Immervoll (Institute for the Study of Labor (IZA), 2005)
The systems of direct taxes and cash benefits in the Member States of the European Union vary considerably in size and structure. We explore their direct impacts on cross-sectional income inequality (termed redistributive effect for the purpose of this paper) using EUROMOD, a tax-benefit microsimulation model for the European Union. This relies on harmonised household micro-data representative of each national population together with simulations of entitlements to cash benefits and liabilities for taxes and social contributions. It allows us to draw a more comprehensive and comparable picture of the combined effects of transfers and taxes than is usually possible. We decompose the redistributive effect of tax-benefit systems to assess and compare the effectiveness of individual policies at reducing income disparities. The following categories of benefits and taxes are considered both individually and in combination: income taxes, social contributions, cash benefits designed to target the poor or redistribute inter-personally (through means-testing) as well as cash benefits intended to redistribute intra-personally across the lifecycle (through social insurance or contingency-based entitlement). We derive results for the 15 old members of the European Union and present them for each country separately as well as for the EU-15 as a whole.
Keywords: C81; D31; H22; H55; 330; income inequality; redistribution; microsimulation; European Union; Haushaltseinkommen; Einkommensverteilung; Einkommensumverteilung; EU-Staaten; Verteilungswirkung